2005
DOI: 10.1890/04-1698
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Effects of Mean Intensity and Temporal Variation of Disturbance on a Rocky Seashore

Abstract: Understanding the extent to which natural assemblages withstand changes in the regime of disturbance has considerable practical and theoretical interest. In this paper we examine the separate and interactive effects of intensity, temporal variation, and spatial extent of disturbance on temporal variance in assemblages of algae and invertebrates of rocky shores in the northwest Mediterranean. Temporal variation of disturbance is a predictor variable in the experiment, while temporal variance in abundance and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
117
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(126 citation statements)
references
References 50 publications
9
117
0
Order By: Relevance
“…This type of response has also been observed in studies focused on predation, where enhanced temporal variability of species abundance and fluctuations in community structure occurred in response to variable regimes (Butler 1989;Navarrete 1996). In contrast, Bertocci et al (2005), studying rocky shore assemblages, found the temporal variance of community structure was reduced by increased temporal variability in disturbance regimes.…”
Section: Balanus Trigonussupporting
confidence: 57%
See 1 more Smart Citation
“…This type of response has also been observed in studies focused on predation, where enhanced temporal variability of species abundance and fluctuations in community structure occurred in response to variable regimes (Butler 1989;Navarrete 1996). In contrast, Bertocci et al (2005), studying rocky shore assemblages, found the temporal variance of community structure was reduced by increased temporal variability in disturbance regimes.…”
Section: Balanus Trigonussupporting
confidence: 57%
“…To overcome this problem and to create experiments that unambiguously separate the mean (of either frequency or intensity) from the temporal variability of a predictor variable, Benedetti-Cecchi (2003) proposed an experimental design in which intensity and variability are treated as fixed, orthogonal factors. Previous work that has manipulated temporal variation in disturbance has used a single patterned sequence of disturbance events through time as a representative for a given level of variation in disturbance (Robinson and Sandgren 1983;Bertocci et al 2005;Benedetti-Cecchi et al 2006). However, there are many different possible sequences of events that would lead to the same overall level of variance for a given treatment .…”
Section: Introductionmentioning
confidence: 99%
“…They thus tend to dominate in rocky habitats exposed to severe abiotic stress, including the mechanical impact of waves (e.g. Bertocci et al 2005), and to intense grazing that can remove potential algal competitors (Steneck 1986, Airoldi 2000, Bulleri et al 2002. As stated above, such favourable abiotic conditions, normally occurring at the study site during the winter might have contributed to present findings on L. incrustans.…”
Section: Discussionmentioning
confidence: 69%
“…Secondly, timing of manual thallus movements was less regular than that of thalli moved by tidal currents. Irregularly applied disturbances were reported to affect benthic community traits differently than regularly applied disturbances of identical overall intensity (Bertocci et al 2005;Wollgast et al 2008). Thirdly, benthic species may benefit moderately from the continuous presence of a thallus.…”
Section: Discussionmentioning
confidence: 99%